Teaching Spatial Thinking with the National Atlas of Korea in U.S. Secondary Level Education - Chu, Gregory H.; Hwang, Chul Sue; Choi, Jongnam (Proceedings of the ICA, 2018)
This paper is predicated on the body of literature that supports a theoretical concept that middle and high school age children possess the cognitive ability to understand thematic maps and achieve some degree of cartographic literacy. In 2006, the US National Research Council (NRC) of the National Academies published a landmark book on Learning to Think Spatially. This book documented essential secondary education components and various aspects of teaching spatial thinking. The NRC defines spatial thinking as “a form of thinking based on a constructive amalgam of three elements: concepts of space, tools of representation, and processes of reasoning” (NRC, 2006, ix). This paper is an attempt to document and understand some of the attributes associated with these three elements. Specifically, it aims to find ways that can effectively contribute to the teaching of these elements associated with spatial thinking. The National Atlas of Korea is chosen for lesson plan development because it is well-designed and provides a range of contents and comprehensiveness that are ideal; in addition, it is freely accessible online and downloadable (http://nationalatlas.ngii.go.kr/). Four master geography teachers were invited to examine the Atlas to conceive and develop Advanced Placement Human Geography (APHG) lesson plans. Four lesson plans were written and have continually been implemented in classrooms to over 800 students in the States of Utah, Georgia, Minnesota, and Tennessee since the 2015 Fall semester. Results are presented in this paper.